2009
DOI: 10.1371/journal.pone.0008228
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Optimal Allocation of Time in Sequential Movements

Abstract: The allocation of limited resources such as time or energy is a core problem that organisms face when planning complex actions. Most previous research concerning planning of movement has focused on the planning of single, isolated movements. Here we investigated the allocation of time in a pointing task where human subjects attempted to touch two targets in a specified order to earn monetary rewards. Subjects were required to complete both movements within a limited time but could freely allocate the available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 42 publications
(61 reference statements)
3
30
0
Order By: Relevance
“…We believe that the observed errors are related to an increase in the specific value of a particular trial within the general context. We did not see increased performance after hits, and this matches the data collected by Wu (Wu et al, 2009). However, we revealed errors related to a reactive effect: competition shows an increased share of errors caused by one's own miss in the previous trial.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We believe that the observed errors are related to an increase in the specific value of a particular trial within the general context. We did not see increased performance after hits, and this matches the data collected by Wu (Wu et al, 2009). However, we revealed errors related to a reactive effect: competition shows an increased share of errors caused by one's own miss in the previous trial.…”
Section: Discussionsupporting
confidence: 90%
“…Other research (Wu et al, 2009) revealed rather ambiguous results, but demonstrated that the way the participants used time given for a specific task is also suboptimal. The participants had to sequentially hit two targets that appeared on the screen within a limited period of time with no specific limitations on time distribution within the task itself.…”
mentioning
confidence: 95%
“…This hypothesis was based, in part, on results in another experiment that demonstrated sub-optimal motor planning in sequential pointing tasks (Wu, Dal Martello, & Maloney, 2009). In the Wu et al study, subjects executed a sequence of hand movements to touch two targets.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, motor decisions concerning planned sequences of movements under risk turn out to be suboptimal. When subjects have a fixed time within which to try to sequentially hit two targets, each associated with a different reward, there is a tradeoff in the time allocated to each movement, and performance is suboptimal [15]. Subjects spend too much time on the first reach even when hits on the second target are far more valuable than on the first.…”
Section: The Cost Of Timementioning
confidence: 99%